Allelopathic effect of Batawali (Tinospora tuberculata) on weeds and vegetative growth of several rice varieties - Zamrillah, Mohamad Syafiq Ashraf (2015)
Weed management using chemical herbicides inevitably results in environmental pollution, herbicide resistance, and harm farmers and ecosystem as well. This study was conducted to evaluate the allelopathic effect of Batawali (T. tuberculata) on weed control and early growth of several rice varieties. T. tuberculata leaves powder was applied as early post-emergence herbicide to four different rice varieties which were MR219, MR220, MR263, and MR269. Data on the percentage of injury or mortality in weeds, number of tillers, plant height, number of leaves, and leaves chlorophyll content were recorded at certain time intervals after T. tuberculata application. Data on the shoot and root dry weights were recorded prior to panicle initiation stage. Application of T. tuberculata powder extract results in good weed control. However, allelopathic effect of T. tuberculata was unable to inhibit the growth of Leptochloa chinensis. Significant differences were obtained on plant height, tillers and leaves production, and shoot and root dry weight between treated and control MR219 variety. Between treated and control MR220 variety, the significant difference obtained was on the production of tillers. Significant differences were obtained on number of tillers, number of leaves, and shoot and root dry weight between treated and control MR263 variety. Between treated and control MR269 variety, the significant differences were obtained on number of leaves, and shoot and root dry weight. In conclusion, allelopathic effect of T. tuberculata results in good weed control. It also has different stimulatory and inhibitory effect on early growth of different rice varieties. MR220 variety had the lowest inhibitory effect among the tested varieties.